(untitled) (Bangladesh Journal of Plant Taxonomy, 2010)
Eight newly recorded taxa of freshwater phytoplankton from Bangladesh have been described in the present paper. Of these, 3 species are from Cryptomonadales, 2 species from each of Volvocales and Euglenales and one species from Chromulinales. In addition one new forma of Pediastrum duplex Meyen var. duplex fa. nagdaensis M.A. Alfasane, M.S. Islam & M. Khondker fa. nov. (Chlorococcales) has also been described in this account. Keywords: Phytoplankton; Chlamydomonas; Pyramidomonas; Pediastrum; Epicystis; Chroomonas. DOI: 10.3329/bjpt.v17i1.5394 Bangladesh J. Plant Taxon. 17(1): 87-92, 2010 (June)